Globalisation and sustainability (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. Globalisation is typically defined "as the increased flow of goods, services, capital, people, and ideas across international boundaries." This integration of economic, social, and cultural activities has resulted in the greater interconnectedness of people, cultures, and economies worldwide. Some significant benefits are associated with globalisation, such as increased trade, greater living standards and improved technology for some. But this is unfortunately not the full story, as it is also linked to adverse effects on the environment, society, and economic stability. In this track, we will explore the connection between globalisation and sustainability and the need for global cooperation to combine the two concepts successfully. We will also examine how the Sustainable Development Goals (SDGs) can guide us towards a brighter, prosperous, and far more sustainable future. Globalisation has enabled us to be more connected to one another than ever. The rapid increase in technological advancements and regional integration has led to the formation of advanced economies. Domestic businesses grow into international ones and further contribute to the spread of technologies. Core aspects of globalisation include increased international trade and cooperation. There is also the concept of 'social globalisation', meaning the transfer of ideas and information between countries. Learning Objectives Identify what globalisation is Examine the links between globalisation and sustainability Discover methods for collective action to combat climate change.